A dynamic evaluation of macao environmental policies based on text mining of the PMC knowledge framework - Rongjiang Cai; Tao Zhang; Xi Wang; Shufang Zhao; Qiaoran Jia (PLoS ONE, 2025)
This study analyzes policy statements issued by the Macao Special Administrative Region government since the handover, employing text mining methods to explore the trajectory of Macao’s environmental policy development. Results indicate that the Macao government has continuously increased investment in ecosystem resources and implemented diversified strategies to establish a comprehensive environmental management system. Furthermore, the government has integrated environmental policies with broader national development strategies, emphasized cultivating environmentally responsible talent, and focused on key areas such as climate change adaptation, pollution prevention and control, ecosystem protection, and sustainable urban development. This study applies the PMC index model for quantitative analysis, using 9 major variables and 50 minor variables to evaluate important environmental policies implemented between 2010 and 2024. Through the combination of text mining and quantitative analysis with the PMC index, detailed evaluations of these policies are provided. With all policies achieving perfect scores in policy evaluation and disclosure but showing weaknesses in timelinessand regional scope.The research utilizes three-dimensional PMC surface diagrams to visualize policy strengths. Additionally, employing multi-dimensional input-output table analysis methods, the study assesses the overall performance of each policy, identifies areas requiring improvement, and offers targeted recommendations. Macao’s environmental policies demonstrate strong transparency and evidence-based design but require enhanced long-term strategic planning and cross-border cooperation mechanisms within the Greater Bay Area framework..